К изучению экологии мухи Вольфарта (Wohlfahrtia magnified Schin.) - Валентин, Е.И. (Вестник зоологии, 1969)
It was established that the general life longevity of one generation of Wohlfahrlia magnified in July —August, 1967, in Kherson region of the Ukraine was equal to 38 days and larva stage — to 3-4 days.
The pupa stage lasts for 15—16 days at the temperature 25—26° and 19—20 days at the temperature 23.5—24.5°. The larva lay at a depth 5.5—6.5 cm. Imago life longevity under the laboratory conditions is equal to 15—17 davs.